Respiratory failure associated with pneumocystis pneumonia: A case report - K, Sunkonkit; S, Reungrongrat; S, Chowsilpa (Biomedical Sciences and Clinical Medicine, 2019)
Pneumocystis jiroveci pneumonia (PJP) is a life-threatening condition and a common opportunistic infection that can occur in an immunocompromised host. We report on a case of PJP in a child who had been diagnosed with a brain tumor and underwent who had undergone prior treatment with chemotherapy, dexamethasone an radiation. She presented with progressive dyspnea, hypoxia and acute respiratory failure. Her condition did not improve and developed into acute respiratory distress syndrome (ARDS). Her chest radiograph showed bilateral diffuse alveolar infiltration.Bronchoscopy and bronchoalveolar lavage (BAL) were done and the result was positive for Pneumocystis jiroveci. PJP should be a concern in patients who have risk factors such as prior treatment with corticosteroids, immunosuppressive agents or chemotherapy, patients with hematologic malignancy, HIV infection, primary immune deficiencies or severe malnutrition, and patients who have had a solid-organ transplant.